Implementasi Pendidikan Karakter Sebagai Kontribusi Pembangunan Generasi Berkelanjutan Bagi Anak Nagari Kampung Dalam - Nuzul Hidayat; Fauziah Salsabil Busro; Alda Putri Utami; Fitri Rahmadani; Winny Abdillah (Edutech Journals, 2023)
Character education are really necessary not only in school but also in home and in the social environment. Along with advances in technology, character education is very important among children nowadays, with the development of gadget technology, it has a very bad influence on inner village children by exemplifying words that are not appropriate to say, so from We took the research object as elementary school (ES) students. The author then explains the method of implementing community service activities which includes observation and psychoeducation. The results and discussion include students' efforts to build educational character through socialization activities, teaching religion, art, and waste management as well as the influence of gadgets. It is hoped that the implementation of character education can form a generation that is responsible and has integrity for a better future. The socialization is intended for grade 4 elementary school (ES) students and the insight test is taken by grade 4 and 6 elementary school (ES) students. This aims to form a sustainable generation for children in the area.